A comparative study on determining the undrained shear strength parameter of soil by using the h-ometer test and the unconfined compression test (UCT) / Ahmad Zaidi Hampden & Maureen Neging - Hampden, Ahmad Zaidi; Neging, Maureen (2007)
There are many new types of equipment developed in the market for soil testing and compaction control ranging from a simple penetration gadget, to more sophisticated high-tech equipment. The prices for these more sophisticated high-tech equipments are relatively very high. The H-Ometer is test equipment which is relatively cheaper and easier to use in terms of operation. Thus, it may provide an alternative in determining the soil parameters if proven to produce reliable results.